Azimuthal Temperature Variations in Iso-Oph 2 from Multifrequency Alma Observations - Carcamo-Vasquez, M (Oxford University Press, 2023)
Environmental effects, such as stellar fly-bys and external irradiation, are thought to affect the evolution of protoplanetary discs in clustered star formation. Previous Atacama Large Millimetre/submillimetre Array (ALMA) images at 225 GHz of the ISO-Oph 2 binary revealed a peculiar morphology in the disc of the primary, perhaps due to a possible fly-by with the secondary. Here, we report on new ALMA continuum observations of this system at 97.5, 145, and 405 GHz, which reveal strong morphological variations. Multifrequency positional alignment allows us to interpret these spectral variations in terms of underlying physical conditions. ISO-Oph 2A is remarkably offset from the centroid of its ring, at all frequencies, and the disc is lopsided, pointing at gravitational interactions. However, the dust temperature also varies in azimuth, with two peaks whose direction connects with HD 147889, the earliest-type star in the Ophiuchus complex, suggesting that it is the dominant heat source. The stellar environment of ISO-Oph 2 appears to drive both its density structure and its thermal balance. © 2023 The Author(s) Published by Oxford University Press on behalf of Royal Astronomical Society.